Enhanced Photoluminescence in Gold Nanoparticles Doped Homogeneous Planar Nematic Liquid Crystals - Chi-Huang Chang; Rong-Ji Lin; Chuen-Lin Tien; Shang-Min Yeh (Advances in Condensed Matter Physics)
This study reported the photoluminescence (PL) of gold nanoparticles (GNPs) doped planar nematic liquid crystals (NLCs) and observed around 64% enhancement in PL intensity with suitable doping amounts of GNPs in liquid crystals 5CB. The enhancement in PL intensity has been attributed to the increased surface area from GNPs, which results in increased emissions due to the increased scattering of excitation. The subsequent decay of PL intensity with doping more amounts of GNPs in liquid crystals 5CB was due to the aggregation of the GNPs, which resulted in decayed emissions due to the decay of the scattering of excitation. The concentration and the size of GNPs, as well as the orientation of the LCs’ director, with respect to the excitation, which depend on the intensity of the PL, were also investigated.